2009
DOI: 10.1007/s00198-009-1030-y
|View full text |Cite
|
Sign up to set email alerts
|

Global vitamin D status and determinants of hypovitaminosis D

Abstract: The list of risk factors for hypovitaminosis D in the Conclusion (first sentence, second paragraph) should include "higher latitude" rather than "lower latitude".The online version of the original article can be found at http://dx.doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
302
5
24

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(353 citation statements)
references
References 0 publications
22
302
5
24
Order By: Relevance
“…This finding concurs with other Canadian studies [12,13,15,[38][39][40] and with international [32] findings. The population of Canadians with darker skin pigmentation now stands at one in five Canadians, and the need for people of darker skin to take more vitamin D is increasingly recognized [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding concurs with other Canadian studies [12,13,15,[38][39][40] and with international [32] findings. The population of Canadians with darker skin pigmentation now stands at one in five Canadians, and the need for people of darker skin to take more vitamin D is increasingly recognized [41].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, levels of serum 25(OH)D <75 nmol/L [22] were evident in 59% [11,12,15,31] and in other countries [32]. Consequently, it is likely that a large proportion of Canadians would have suboptimal vitamin D status at some point during the year.…”
Section: Discussionmentioning
confidence: 58%
“…The latter indicates that commonly used supplement doses are inadequate to ensure optimal vitamin D nutrition. Taken together with previous studies in Caucasians [17][18][19][20], Asians [21][22][23][24][25], and other men [17,26,27] confirm the observation that vitamin D deficiency and/or insufficiency is endemic among populations of the world, and countries with sunny climates are no exception.…”
Section: Discussionsupporting
confidence: 85%
“…Strong positive correlation of BMI with BMD at all sites and negative correlation with PTH, ALP, and phosphates seen in the present study was also observed by several other workers [6,7,39]. There was no significant correlation observed between serum 25(OH)D and BMD at different sites which is in concordance with our earlier studies [8-11, 13, 32].…”
Section: Calcaneum Bmdsupporting
confidence: 92%